{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Stitz-Zeager_College_Algebra_e-book

# Hence we may write y x which describes the slope as

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 4 3 2 1 −4 −3 −1 (−2, 0) −1 −2 1 3 4 x (2, 0) (4, −2) −3 −4 The graph of y = f (x) (a) y = f (x) − 1 (d) y = f (2x) (g) y = f (x + 1) − 1 (b) y = f (x + 1) (e) y = −f (x) (h) y = 1 − f (x) (f) y = f (−x) (i) y = 1 f (x + 1) − 1 2 (c) y = 1 2 f (x) 2. The complete graph of y = S (x) is given below. Use it to graph the following functions. y (1, 3) 3 2 1 (−2, 0) −2 (0, 0) −1 1 (2, 0) x −1 −2 −3 (−1, −3) The graph of y = S (x) (a) y = S (x + 1) 1 (c) y = 2 S (−x + 1) (b) y = S (−x + 1) (d) y = 1 S (−x + 1) + 1 2 1.8 Transformations 105 3. The complete graph of y = f (x) is given below. Use it to graph the following functions. y 3 (0, 3) 2 1 −3 −2 −1 (−3, 0) 1 −1 (c) j (x) = f x − 3 (3, 0) x (g) d(x) = −2f (x) (a) g (x) = f (x) + 3 (b) h(x) = f (x) − 2 1 2 2 3 2 3x − 1 f (3x) 4 (h) k (x) = f (i) m(x) = (d) a(x) = f (x + 4) (j) n(x) = 4f (x − 3) − 6 (e) b(x) = f (x + 1) − 1 (k) p(x) = 4 + f (1 − 2x) (f) c(x) = 3 5 f (x) (l) q (x) = − 1 f 2 x+4 2 −3 √ 4. The graph of y =...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online